Analysis of the state of highly skilled football players’ musculoskeletal system at the beginning of the 2nd preparatory period of the annual macrocycle - Kokareva, S.; Kokarev, B.; Doroshenko, E. Yu.; Кокарева, С.; Кокарев, Б.; Дорошенко, Едуард Юрійович (My University, 2018)
Background. Nowadays the development of adequate means of effective rehabilitation of athletes’ organism after training and competitive load is becoming more and more an urgent task of sports training. It is well known that during training and competitive activity they can reach critical values. Thus, the optimization of the system of complex athletes’ recovery is the basis for maintaining a high level of working capacity and preventing the negative consequences of overstrain during training and competitive loads. Objective. This research aims to determine the functional state of the musculoskeletal system (MSS) of highly qualified football players at the beginning of the 2nd preparatory period of the annual training cycle. Methods. Analysis of scientific and methodological literature, flexibility testing, stabilometry, methods of mathematical statistics. Results. It is established that at the beginning of the 2nd preparatory period of an annual preparation cycle the flexibility indicators’ level of examined athletes were characterized as «low» or «below the average». It is shown that in this period of the annual macrocycle the high qualified football players’ level of static ability to support corresponded to the value «average» and «below average», as well as joint mobility indicators. The facts of vestibular and proprioceptive disturbances were revealed. Such disturbances have a significant impact on the equilibrium function. Conclusions. According to the results of motor tests and goniometry, the low level of the functional state of the football players’ MSS after the winter vacation indicates the inelasticity or shortening (spasm) of the muscles and ligamentous apparatus, which is one of the signs of their chronic overstrain. The previously obtained experimental data on the reduction of stabilometric parameters which characterize the stability of the vertical posture, instability of the joints of the lower extremities, the presence of vestibular and proprioceptive disturbances were confirmed by current research. Also our research expanded the views about preventive measures and leveling the negative effects of overload of highly qualified football players’ MSS. It is recommended to include corrective and preventive exercises (myofascial relaxation(MFR) methods) in the preparatory and final parts of the training sessions. This technique will help to normalize the functional state of the MSS and to reduce the risk of injury. Актуальність. Усе більш актуальним завданням спортивної підготовки сьогодення стає розробка адекватних засобів ефективного відновлення працездатності організму спортсменів після тренувальних і змагальних навантажень. Загальновідомо, що під час тренувань і змагальної діяльності вони можуть досягати критичних величин. Отже, оптимізація системи комплексного відновлення спортсменів є основою для збереження високого рівня працездатності й запобігання негативним наслідкам перенапруження під час тренувальних і змагальних навантажень. Мета дослідження – визначення функціонального стану опорно-рухового апарату (ОРА) висококваліфікованих футболістів на початку 2-го підготовчого періоду річного циклу підготовки. Методи дослідження – аналіз науково-методичної літератури, тестування гнучкості, стабілометрія, методи математичної статистики. Результати роботи. Установлено, що на початку 2-го підготовчого періоду річного циклу підготовки піддослідні спортсмени характеризувалися «низьким» або «нижчим від середнього» рівнем показників гнучкості. Показано, що у футболістів високої кваліфікації рівень статичної опороспроможності в цьому періоді річного макроциклу відповідав значенням «середнє» та «нижче від середнього», так само, як і показники суглобової рухливості. Виявлено факти вестибулярних і пропріоцептивних порушень, які суттєво впливають на функцію рівноваги. Висновки. Згідно з результатами рухових тестів та гоніометрії низький рівень функціонального стану ОРА футболістів після виходу із зимової відпустки свідчать про нееластичність або скороченість (спазмування) м’язів і зв’язкового апарату, що є однією з ознак їх хронічного перенапруження. Чинним дослідженням підтверджено раніше отримані експериментальні дані про зниження стабілометричних показників, що характеризують стабільність вертикальної пози, нестабільність суглобів нижніх кінцівок, наявність вестибулярних і пропріоцептивних порушень; розширено уявлення про заходи попередження та нівелювання негативних наслідків перевантаження ОРА висококваліфікованих футболістів. Рекомендовано включати до підготовчої й завершальної частин навчально-тренувальних занять коригувальні та профілактичні вправи за наявними методиками міофасциального розслаблення (МФР), які сприятимуть нормалізації функціонального стану ОРА й зниженню ризику травматизму.
Аналіз стану опорно-рухового апарату висококваліфікованих футболістів на початку 2-го підготовчого періоду річного макроциклу
Keywords: football players; functional state; musculoskeletal system; flexibility; quality level; футболісти; функціональний стан; опорно-руховий апарат; гнучкість; якісний рівень